MAPPING INDIA’S COMMODITY EXPORT NETWORK: SECTORAL INTERCONNECTEDNESS AND BEHAVIOR AT TAIL DISTRIBUTION WITH LEADING GLOBAL ECONOMIES (IITM Journal of Business Studies, 2025)
This study investigates the interconnectedness  of India’s commodity exports with thirteen  major global economies from 2000 to 2023,  employing the quantile-quantile connectedness  approach. The analysis, illustrated through an  extensive network graph, highlights significant  variations and dependencies across three  economic indicators, particularly in extreme  distribution scenarios across various export  categories. Our findings reveal convoluted non linear and multiscale interdependencies that  elucidate global economic behavior, especially  in India’s bilateral trade relationships. Economic  Policy Uncertainty (EPU), Consumer Price  Index (CPI), and Producer Price Index (PPI) of  destination countries have a decisive role in the  export network, alongside key export categories  such as Petroleum, Agriculture, Ores, and  Manufacturing, underscoring India’s pivotal role  within the global commodity export network.  Furthermore, Principal Component Analysis  (PCA) is utilized to consolidate economic  variable outcomes into a singular, interpretable  metric for each commodity category. These  results underscore the significance of extreme  economic conditions and tail dependencies  in shaping policy, with critical implications  for international trade and economic strategy.  This study’s methodological and sector-specific  insights offer valuable guidance to policymakers  and economists in understanding global  economic interdependence and crafting more  resilient trade and economic policies.
Keywords: Quantile-Quantile Connectedness; Economic Interdependence; Network Graphs; Merchandise Trade; Global Economies; Non Linear Interconnections; Export Network